An experimental study on flexural behaviour of large-scale concrete beams incorporating crumb rubber and steel fibres. (15th August 2017) - Ismail, Mohamed K.; Hassan, Assem A.A.
Highlights: Flexural behaviour of large-scale CR beams up to 35% replacement was investigated. The beneficial effect of combining CR and SFs (35 and 60 mm) was studied. Combining CR and SFs provides promising sustainable composite for structural use. Up to 15% CR can be used in multiple applications with no structural concerns. Using 1% SFs extended the possible structural use of CR up to 35% replacement. Abstract: Twelve self-consolidating and vibrated concrete mixtures were developed to investigate the effect of crumb rubber (CR) with/without steel fibres (SFs) on flexural behaviour of large-scale beams. The main parameters were the percentage of CR (0–35% by volume of sand), volume of SFs (0%, 0.35%, and 1%), and length of SFs (35 mm and 60 mm). The performance of some code design equations was evaluated in predicting the cracking moment and flexural capacity of the tested beams. The results showed that increasing the CR appeared to narrow the crack widths, reduce self-weight of concrete, and improve deformability at a given load. On the contrary, the addition of high percentages of CR (above 15%) showed a significant reduction in the ductility, toughness, first crack moment, and ultimate flexural capacity of the tested beams. However, adding 1% SFs (35 mm) helped to increase the possible safe content of CR to 35%, achieving concrete beams with further reduction in self-weight and with sufficient flexural capacity, ductility, and toughness for multiple structural applications. The results also indicated that the investigated design equations conservatively predicted the flexural capacity of the tested beams but overestimated the first cracking moment.